Management of breast papillary lesions diagnosed in ultrasound‐guided vacuum‐assisted and core needle biopsies. Issue 4 (20th January 2015) - Yamaguchi, Rin; Tanaka, Maki; Tse, Gary M; Yamaguchi, Miki; Terasaki, Hiroshi; Hirai, Yoshitake; Nonaka, Yasuhide; Morita, Michi; Yokoyama, Toshiro; Kanomata, Naoki; Naito, Yoshiki; Akiba, Jun; et al.
<x xml:space="preserve">Abstract</x> Aims To assess the outcome of breast papillary lesions diagnosed by ultrasound‐guided core needle biopsy (CB) or vacuum‐assisted 'mammotome' biopsy (MT), the accuracy of these diagnoses, and whether it is justified not to undertake surgical excision of non‐malignant papillary lesions so diagnosed. Methods and results Among 3219 (MT, 2195; CB, 1024) breast biopsies spanning 5 years, 185 (5.7%) papillary lesions [MT, 162 (88%); CB, 23 (12%)] were identified. Of these, 142 cases (77%; MT/CB, 125/17) were benign, 24 (13%, 23/1) were atypical, and 19 (10%; 14/5) were malignant. Of the 142 benign cases, 114 had imaging follow‐up (FU) (FU period 2–81 months); 17 of 114 cases were excised, and four were malignant (3.5%) (FU period 4–57 months). Of the 24 atypical cases (23 had FU), 19 were excised: six were benign (32%) and 13 malignant (68%). The remaining four cases were considered to be non‐malignant (FU period 7–54 months). Conclusions Benign papillary lesions diagnosed by MT or CB might not require immediate excision, but should receive imaging FU for at least 5 years. Excision should be performed in cases showing changes in imaging features, as the possibilities of carcinoma coexisting with papilloma or carcinoma developing from papilloma cannot be excluded, as illustrated by the 4% upgrade rate at excision in this study.